Pelatihan Komputer sebagai Upaya Meningkatkan Kesiapan Anak Menghadapi Era Digital di Desa Ladang Peris Bajubang - Sukatin Sukatin; Maisarah Gusvita; Julia Julia; Retno Widari; Septia Ningsih; Reza Apriyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This computer training is part of Community Service (PKM) in Ladang Peris Village, Bajubang District, with the aim of improving children's readiness to face the digital era. The main problem is low technological skills due to limited facilities and minimal access to training. In addition, the lack of understanding about the wise use of technology is also an important issue. This training aims to provide basic computer skills education and increase awareness of the benefits and risks of technology. The main target is elementary to secondary school children who are interested in learning technology but have limited facilities. The methods used include theory, direct practice, and interactive approaches. Theoretical materials include an introduction to hardware, software, and the impact of technology. Practice is carried out through typing activities, using educational applications, digital drawing, and safe internet exploration. The results of the training showed an increase in children's understanding of technology and their courage to use it. They are also more aware of the importance of using technology positively. In conclusion, this training has a positive impact by providing children with basic computer skills, preparing them to face digital challenges, and encouraging the sustainability of the program to create a young generation that is technologically literate.